Aplicação da computação gráfica por meio da elaboração de maquetes digitais utilizando sketchup - Silvestre, Guilherme Augusto Astolfi [UNESP] (2018)
Computer Graphics is the area of Computer Science responsible for the creation and manipulation of both bi and three-dimensional images. Numerous CAD software currently enables researchers in the area of Computer Graphics to create, represent and process their products virtually through three-dimensional digital modeling. Considering that these programs provide increasingly sophisticated techniques for the development of complex digital artifacts, and that digital modeling is a very widespread technique used for building projects, the purpose of this work is the use of a CAD software for the construction of the digital model of the Laboratories of Education, Research and Extension in Computing (LEPEC) located at UNESP Câmpus Bauru. For this, the reader will be introduced to the concepts of digital modeling, architectural conventions, rendering, post-production and photorealism.